A method to assess lifetime dietary risk: Example of cadmium exposure. (March 2020) - Pruvost-Couvreur, Manon; Le Bizec, Bruno; Béchaux, Camille; Rivière, Gilles
Abstract: Usually health risk related to food contaminants is assessed based on consumption data collected on a few days. Consequently, this approach considers neither the evolution of exposures over time nor the potential accumulation of the substance. The aim of the present study was to develop a method to assess lifetime dietary risk due to cadmium exposure. Three methods were compared, respectively based on age, dietary pattern and sociodemographic characteristics. Additionally, exposure trajectories were converted into cadmium body burden trajectories using a PBTK-TD model ultimately predicting the occurrence of renal effects. It was shown that dietary exposures to cadmium, as well as exceedances of health based guidance values, greatly vary with age and individual profiles. The developed methods allowed identifying parameters affecting dietary exposure to cadmium and distinguishing at-risk subpopulations. Furthermore, this study demonstrated that it is necessary to consider individual changes through life and kinetic of the substance to assess risk properly. Highlights: Three methods are proposed to assess lifetime health risk from individual behaviours. Simulations take into account age, dietary pattern and sociodemographic parameters. Developed methods distinguished at-risk subpopulations. Food contaminant kinetics must be considered in lifetime risk assessment. Dietary exposure to cadmium of some simulated individuals led to renal injuries.